CGIAR’s contribution to peace: Portfolio Analysis - Liebig, Theresa Ines; Läderach, Peter R.D.; Nguyen, Nam; Pacillo, Grazia; Zuali, Lalhmangaih; Quinn, Sarah (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
We conducted a portfolio analysis of CGIAR‘s ongoing portfolio that has potential to contribute to the prospects of peace. This portfolio analysis comprised two main working steps: 1) Information generation and 2) Visualization of portfolio results.